KONDISI KESEHATAN EKOSISTEM MANGROVE SEBAGAI SUMBER POTENSIAL PENGEMBANGAN EKONOMI KREATIF PESISIR SELAT SUNDA - Adi Susanto; Muta Ali Khalifa; Erik Munandar; Hery Sutrawan Nurdin; Hendrawan Syafrie; Fahresa Nugraheni Supadminingsih; Afifah Nurazizatu Hasanah; Bathara Ayi Meata; Ririn Irnawati; Ani Rahmawati; Achmad Noerkhaerin Putra; Toufik Alansar; Julian Saputra; Bakti Sulistyono; Ahmad Raihan (Pusat Unggulan Iptek Ketahanan Pangan Universitas Sultan Ageng Tirtayasa, 2022)
The functions and benefits of the existence of the mangrove ecosystem are strongly influenced by their health conditions. Ideally, a healthy mangrove ecosystem will provide greater ecological, economic, and service benefits. This study aims to determine the health condition of the mangrove ecosystem as a first step for disaster mitigation and productive economic development in the coastal area of the Sunda Strait. Data collection was carried out in November-December 2021 using the MonMang application in five different villages. The results showed that the highest diversity of mangrove species was found in Cigorondong Village with 9 species including Acanthus ilicifolius, Avicennia marina, Aegiceras corniculatum, Derris trifoliata, Sonneratia caseolaris, Excoecaria agallocha, Lumnitzera racemosa, Ceriops tagal, Heritiera littoralis. The highest canopy cover (79%) was found in the mangrove ecosystem in Citeureup Village and the highest tree density was found in Cigorondong Village at 3,300 individuals/ha. The health condition of the mangrove ecosystem on the coast of the Sunda Strait is moderate because the MHI value obtained is in the range of 33-63%.